KOMPARASI HASIL BELAJAR SISWA MENGGUNAKAN STRATEGI MAKE A MATCH DANCARD SORT MATA PELAJARAN AKIDAH AKHLAK KELAS X MADRASAH ALIYAH - Faridhotul Zahro’; Ju’Subaidi Ju’Subaidi (IAIN Ponorogo, 2020)
The purpose of this study was to find out the difference between student learning outcomes using the make a match strategy and Card Sort strategy in the subjects of AkidahAkhlaq on X grade students in Aliyah Madrasah. This research is a quantitative research with comparative analysis. The subjects of this study were26 X grade studentsof MA M'arifBalong. Data collection used test instruments, while data analysis techniques used the